2023
DOI: 10.3389/fimmu.2023.1217809
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of HLA-E and HLA-G on genetically modified porcine endothelial cells attenuates human NK cell-mediated degranulation

Abstract: Natural killer (NK) cells play an important role in immune rejection in solid organ transplantation. To mitigate human NK cell activation in xenotransplantation, introducing inhibitory ligands on xenografts via genetic engineering of pigs may protect the graft from human NK cell-mediated cytotoxicity and ultimately improve xenograft survival. In this study, non-classical HLA class I molecules HLA-E and HLA-G were introduced in an immortalized porcine liver endothelial cell line with disruption of five genes (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Several studies have shown that porcine cells expressing non-classical HLA class I molecules, including HLA-E and/or HLA-G, can protect porcine cells from human NK cell cytotoxicity [35][36][37]. Further, our recent study indicated that co-expressing HLA-E and HLA-G on porcine cells effectively inhibits human NK cell activation [29].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Several studies have shown that porcine cells expressing non-classical HLA class I molecules, including HLA-E and/or HLA-G, can protect porcine cells from human NK cell cytotoxicity [35][36][37]. Further, our recent study indicated that co-expressing HLA-E and HLA-G on porcine cells effectively inhibits human NK cell activation [29].…”
Section: Discussionmentioning
confidence: 76%
“…NK cell activation was assessed by CD107a degranulation assays as previously reported [29]. Buffy coats were purchased from Versiti Indiana Blood Center.…”
Section: Human Nk Cell Activation In Response To Porcine Endothelial ...mentioning
confidence: 99%
“…The use of genetic engineering to express on pig cells inhibitory ligands such as nonclassical human leukocyte antigens HLA-E and -G can be a strategy to overcome NK responses in xenotransplantation. Indeed, at least in vitro, co-expression of both these HLA molecules on pig cells is associated with a significant reduction of human NK cell degranulation [ 19 ].…”
Section: Immunological Challengesmentioning
confidence: 99%
“…Considerable discussion surrounds the reactivity of antibodies to human leukocyte antigens (HLAs) and swine leukocyte antigens (SLAs) in the immunomodulatory pathway post‐xenotransplantation. The co‐expression of HLA‐E and HLA‐G on genetically modified porcine endothelial cells was observed to attenuate human natural killer (NK) cell‐mediated degranulation 30 …”
Section: Modifications To the Xenograftmentioning
confidence: 99%